Investigation of reheat post- processing using fused filament fabrication (FFF) method - Jay Nelson Segilit (2022)
Production in additive manufacturing (AM) must meet customer demand and satisfaction. Thus, producing the highest quality product is needed to implement, and one way to improve the quality of the product is by implementing post-processing. One of the post-processing that is not usually used is reheating, and this paper discusses the effect of reheat post-processing on the 3D model. The first thing that can be done is to model the heating plate on the engineering software and perform a thermal analysis to see the suitable distance between the heating plate and the 3D model and exposure time before the specimen goes to a melting state. For information, the specimen material used is polylactic acid (PLA). The installation of the heating plate on the 3D printer will be done after the thermal analysis is carried out. The specimen will be printed and reheated and will be tested to see the surface roughness of the specimen that has been reheated and analyzed accordingly. From the thermal analysis conducted, for thin specimens, the suitable distance between heating plate and specimen is 3 cm and below, where the exposure time should be less than 300 s. The specimen will become smoother after testing with a surface roughness machine and a surface image, but based on the findings, after a certain temperature, the specimen will bend, so we can say that it is not suitable for thin layer specimens or models. The best exposure time for this project is 300 s, with a distance of 1.3cm between the heating plate and the specimen. The surface image testing is done to observe the layer line or bead when the distance between the heating plate and specimen is at 1.7cm.